2021
DOI: 10.1016/j.jseaes.2021.104775
|View full text |Cite
|
Sign up to set email alerts
|

The first systematic description of Cambrian fossils from Myanmar: Late Furongian trilobites from the southern part of the Shan State and the early Palaeozoic palaeogeographical affinities of Sibumasu

Abstract: The existence of late Cambrian (Furongian) trilobites in Myanmar (Burma) has been acknowledged since the 1970s, but no formal systematic descriptions of such fossils have been published to date. Herein, we provide such descriptions of some trilobites from the Molohein Group's Myet-Ye Formation from the Linwe area, Ye-Ngan Township of the southern Shan State. Three species from two genera are reported: Asioptychaspis (A. asiatica, previously known from the North China Block, and a new species, A. lata) and Eosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 119 publications
(189 reference statements)
1
18
0
Order By: Relevance
“…Based on the assumption that the Simao terrane was part of Palaeozoic Indochina, strong biotic ties between this region and South China have been suggested from the Ordovician (Zhou et al 1998) through the early Silurian (Wang & Zhang, 2010), with sufficient proximity for conspecific land plant spores in both Simao and South China. Wang et al (2014) suggested an early Palaeozoic link between Simao and the Tethyan Himalaya based on detrital zircon age distributions, and here we note that their figure 3 shows a marked unconformity between the Cambrian and Ordovician, as also evident in the Himalaya, the Lhasa block and in Baoshan, but not in the remainder of Sibumasu (Wernette et al 2021). However, as noted above, Simao apparently docked with the Trường Sơn terrane in the Triassic period, and so its earlier history is not directly relevant to the early location terranes that ultimately became part of Indochina.…”
Section: Discussionsupporting
confidence: 64%
“…Based on the assumption that the Simao terrane was part of Palaeozoic Indochina, strong biotic ties between this region and South China have been suggested from the Ordovician (Zhou et al 1998) through the early Silurian (Wang & Zhang, 2010), with sufficient proximity for conspecific land plant spores in both Simao and South China. Wang et al (2014) suggested an early Palaeozoic link between Simao and the Tethyan Himalaya based on detrital zircon age distributions, and here we note that their figure 3 shows a marked unconformity between the Cambrian and Ordovician, as also evident in the Himalaya, the Lhasa block and in Baoshan, but not in the remainder of Sibumasu (Wernette et al 2021). However, as noted above, Simao apparently docked with the Trường Sơn terrane in the Triassic period, and so its earlier history is not directly relevant to the early location terranes that ultimately became part of Indochina.…”
Section: Discussionsupporting
confidence: 64%
“…According to this view, both the Southern Qiangtang and Baoshan terranes were likely adjacent to western Greater India (Figure 4), and Baoshan was separated from other part of Sibumasu by the intervening Lhasa terrane. Such a separation might explain why Baoshan is the only part of Sibumasu terrane to show a local Cambrian–Ordovician unconformity (cf., Wernette et al., 2021). These observations suggest that during or prior to Permo‐Carboniferous time, several adjacent continental fragments made up an elongate strip located peripheral to the eastern Gondwanan core from west to east, including the Southern Qiangtang, Baoshan, Lhasa, and Sibumasu terranes (Figure 4).…”
Section: Paleogeographic Reconstruction Of the Paleozoic Lhasa Terranementioning
confidence: 99%
“…It is generally accepted that the strata in the Lhasa, and Southern Qiangtang terranes, and Greater India record a marked Cambrian–Ordovician angular unconformity (cf., Myrow et al., 2010; Hu et al., 2021), suggesting the paleogeographic links between them. In contrast, the Sibumasu terrane strongly resembles NW Australia (i.e., the Canning basin) in the lowermost Ordovician stratigraphic succession from clastics to carbonates, and in the latest Cambrian sedimentary succession and shared elements of its trilobite fauna (Wernette et al., 2020a, 2020b, 2021). This history allies Sibumasu and NW Australia at this time, but the status of the Baoshan terrane, commonly considered part of Sibumasu, remains to be clarified.…”
Section: Paleogeographic Reconstruction Of the Paleozoic Lhasa Terranementioning
confidence: 99%
“…The first systematic study of Cambrian fossils from Myanmar was done only recently (Wernette et al . 2021), and no notable fossils have been discovered in the tectonically altered Cambrian rocks of northern Thailand (Wongwanich et al . 2002).…”
Section: Figmentioning
confidence: 99%